2022
DOI: 10.1111/pbi.13812
|View full text |Cite
|
Sign up to set email alerts
|

OsHIPL1, a hedgehog‐interacting protein‐like 1 protein, increases seed vigour in rice

Abstract: The cultivation of rice varieties with high seed vigour is vital for the direct seeding of rice, and the molecular basis of regulation of seed vigour remains elusive. Here, we cloned a new gene OsHIPL1, which encodes hedgehog-interacting protein-like 1 protein as a causal gene of the major QTL qSV3 for rice seed vigour. OsHIPL1 was mainly localized in the plasma membrane and nucleus. RNA sequencing (RNA-seq) revealed that the ABA-related genes were involved in the OsHIPL1 regulation of seed vigour in rice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…In legumes, ABSCISIC ACID INSENSITIVE5 (ABI5) regulated late seed maturation by influencing longevity and RFO accumulation [53]. In rice, it was found that OsHIPL1 mutants, which regulated seed vigor, had higher levels of endogenous ABA in germinated seeds, with two ABA biosynthesis genes (OsZEP and OsNCED4) up-regulated and one ABA catabolism gene, OsABA8ox3 down-regulated [54]. Our study revealed that they might have a potential function in seed storability regulation by affecting hormone homeostasis.…”
Section: The Importance Of Diterpenoid Synthesis Pathway In Seed Stor...mentioning
confidence: 99%
“…In legumes, ABSCISIC ACID INSENSITIVE5 (ABI5) regulated late seed maturation by influencing longevity and RFO accumulation [53]. In rice, it was found that OsHIPL1 mutants, which regulated seed vigor, had higher levels of endogenous ABA in germinated seeds, with two ABA biosynthesis genes (OsZEP and OsNCED4) up-regulated and one ABA catabolism gene, OsABA8ox3 down-regulated [54]. Our study revealed that they might have a potential function in seed storability regulation by affecting hormone homeostasis.…”
Section: The Importance Of Diterpenoid Synthesis Pathway In Seed Stor...mentioning
confidence: 99%
“…Physiological analysis revealed that qSE3 improved seed germination and seedling establishment against salinity stress through mediating seed physiological states, including increasing K + and Na + uptake, promoting abscisic acid (ABA) biosynthesis, and reducing reactive oxygen species (ROS) accumulation. Very recently, OsHIPL1 , which encodes a hedgehog-interacting protein-like 1 protein, was cloned as a causal gene for the major QTL qSV3 associated with rice SV ( He et al., 2022 ). And OsHIPL1 may play its role by modulating ABA levels and OsABIs expression during rice seed germination.…”
Section: Introductionmentioning
confidence: 99%
“…ABA is the other major phytohormones in seed development and seed vigor regulations. It reported that OsHIPL1 protein may modulate endogenous ABA levels and altering OsABIs expression and interacts directly with OsPIP1;1 to affect seed vigor in rice ( He et al, 2022 ), we analyzed the expression of OsHIPL1 and OsPIP1;1 in the HL and LL varieties ( Supplementary Figures 5A,B ), unfortunately, their expression levels have no difference between two varieties, suggesting the differences between the reverse genetic method and the forward genetic method (e.g., transcriptomic analysis). We also identified several long-lived mRNAs with unknown functions, which might be the missed or omitted regulators in rice longevity.…”
Section: Discussionmentioning
confidence: 99%